Trochanteric osteotomy in revision total hip arthroplasty. Issue 8 (3rd August 2020) - Sundaram, Kavin; Siddiqi, Ahmed; Kamath, Atul F.; Higuera-Rueda, Carlos A.
Abstract : Trochanteric osteotomy is a technique that allows expanded exposure and access to the femoral canal and acetabulum for a number of indications. There has been renewed interest in variants of this technique, including the trochanteric slide osteotomy (TSO), extended trochanter osteotomy (ETO), and the transfemoral approach, for both septic and aseptic revision total hip arthroplasty (THA). Osteotomy fixation is crucial for achieving union, and wire and cable-plate systems are the most common techniques. TSO involves the creation of a greater trochanter fragment with preserved abductor attachment proximally and vastus lateralis attachment distally. This technique may be particularly useful in the setting of abductor deficiency or when augmented acetabular exposure is needed. ETO is a posterior-laterally based extensile approach that has been successfully utilized for aseptic and septic indications; most series report a greater than 90% rate of union. The transfemoral approach, as known as the Wagner osteotomy, is an extensile femoral approach and is more anterior-based than the alternate posterior-based ETO. It may be particularly useful for anterior-based approaches and anterior femoral remodelling; rates of union after this approach in most reports have been close to 100%. Cite this article: EFORT Open Rev 2020;5:477-485. DOI: 10.1302/2058-5241.5.190063